Simulação Computacional Aplicada à Sistemas 2D: Design de Redes via Impurezas e Defeitos em Eletrenos - Borher, Felipe Amorim (2023)
This dissertation focuses on the study of two-dimensional (2D) materials using computational simulations and first-principles methods (Ab initio), with the aim of investigating the electronic and thermodynamic properties of the Ca2N electride, which has already been synthesized in its 2D phase. The study of this material is significant due to its unique properties. The electrides in question are ionic crystals where electrons play the role of anions, thus called anionic electrons (AE), which make them promising candidates for a wide range of applications. To carry out this research, we used first-principles methods and density functional theory (DFT) to solve the Kohm-Sham equation. Specifically, we studied the electronic and thermodynamic properties of Ca2N in the form of single and multilayer, as well as the effects of defects in its crystal lattice and the adsorption of metallic and non-metallic atoms on its surface. Our findings indicate that Ca2N exhibits interesting electronic and thermodynamic properties in both single-layer and multilayer forms, such as low workfunction and negative adsorption energies, also we have found that defects and adsorption have significant effects on its properties. Specifically, we discovered that defects can introduce sites containing local magnetization, while adsorption can modify its electronic properties and even induce a metal-semiconductor and metal-halfmetal transition.